PENGEMBANGAN LKPD INTERAKTIF BERBASIS KEARIFAN LOKAL PADA MATERI MAGNET SDN MANGUNJAYAN - Sari Wakhitriyani; Azamul Fadly Noor Muhammad (STKIP Subang, 2025)
Conventional student worksheets (LKPD), widely used in elementary schools, have been shown to have no significant impact on science learning outcomes in the classroom. This situation is even more pronounced when these LKPDs are used in differentiated learning that employs more than one learning method. Therefore, researchers developed an interactive digital LKPD based on local wisdom that can be used in digitally differentiated learning via PCs or smartphones. This study employed the Dick and Carey research and development model. The instruments used included interviews, questionnaires, and tests. The results produced an interactive LKPD based on local wisdom for science learning. Based on the analysis of pre-test and post-test results, there was a significant increase in student learning outcomes, with satisfactory final results. Therefore, it can be concluded that the interactive LKPD based on local wisdom is capable of improving student science learning outcomes in elementary schools.